2018
DOI: 10.1016/j.physbeh.2017.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rat parental morphine exposure on passive avoidance memory and morphine conditioned place preference in male offspring

Abstract: Drug addiction is a chronic disorder resulted from complex interaction of genetic, environmental, and developmental factors. Epigenetic mechanisms play an important role in the development and maintenance of addiction and also memory formation in the brain. We have examined passive avoidance memory and morphine conditioned place preference (CPP) in the offspring of male and/or female rats with a history of adulthood morphine consumption. Adult male and female animals received chronic oral morphine for 21days a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 46 publications
1
18
0
Order By: Relevance
“…Besides, mu, kappa and delta opioid receptors are found in oocytes, which may be involved in the trans-generational inheritance of addiction (Yohn et al, 2015). Furthermore, previous studies have shown that altered response to morphine is transmittable to the next generation of morphine administered rats (Akbarabadi et al, 2018;Byrnes, 2005;Byrnes et al, 2013). Physiological and organic alterations in the brain of the progeny of morphine exposed parents have also been reported (Cicero et al, 1991;Sarkaki et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, mu, kappa and delta opioid receptors are found in oocytes, which may be involved in the trans-generational inheritance of addiction (Yohn et al, 2015). Furthermore, previous studies have shown that altered response to morphine is transmittable to the next generation of morphine administered rats (Akbarabadi et al, 2018;Byrnes, 2005;Byrnes et al, 2013). Physiological and organic alterations in the brain of the progeny of morphine exposed parents have also been reported (Cicero et al, 1991;Sarkaki et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Conditioned place preference (CPP) was developed as a technique to assess the reinforcing properties of opioid drugs (Rossi and Reid, 1976 ; Katz and Gormezano, 1979 ; Mucha and Iversen, 1984 ). Now, CPP is widely used to test context associations based on the rewarding properties of an unconditioned stimulus in many organisms including, rodents (Lu et al, 2005 ; Akbarabadi et al, 2018 ; Cunningham, 2019 ), flies (Kaun et al, 2011 ), C. elegans (Musselman et al, 2012 ; Engleman et al, 2018 ), planaria (Hutchinson et al, 2015 ; Mohammed Jawad et al, 2018 ; Adams and Byrne, 2019 ; Phelps et al, 2019 ), primates (Wang et al, 2012 ; Borges et al, 2015 ; Yan et al, 2015 ; Wu et al, 2016 ), and humans (Thewissen et al, 2006 ; Childs and De Wit, 2009 , 2013 , 2016 ). Although a widely used behavioral model, CPP is a complex behavior that incorporates Pavlovian learning, memory, and motivated behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Wistar albino rats, weighing between 200 to 220 grams were purchased from Pasture Institute, Tehran, Iran. The rats were exposed to morphine according to a modified protocol of Akbarabadi and colleagues (2018[3]). The total of 32 males and 32 females were used for mating and morphine treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Twenty-four male and twenty-four female Wistar rats were exposed to the treatment of oral morphine sulfate according to the protocol described earlier (Akbarabadi et al, 2018[3]). Morphine was given in the drinking fluid in the range of 0.1 to 0.4 mg.ml -1 in 48 intervals for up to three weeks (Figure 1A(Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation